The effects of embedding social identities on perceived leadership outcomes and the intentional mobilization of group members. (March 2021) - Evans, Andrew L.; Slater, Matthew J.; Edwards, Michael
Abstract: According to Identity Leadership, effective leaders make the group matter by embedding social identities in material reality. Across two studies, we explored the potential importance of embedding social identities on group members' perceptions of leader trust, influence, conflict and intentional mobilization. In Study 1, 74 competitive varsity athletes read a vignette describing a coach who was either embedding or not embedding social identities. Participants presented with a coach who was embedding social identities reported significantly greater leader trust, leader influence and intentional mobilization, and significantly lower leader conflict. In Study 2, four football teams each comprising six athletes were assigned to one of two quasi-experimental conditions where a coach either: (1) spent two weeks embedding social identities before spending two weeks not embedding them; or (2) spent two weeks not embedding social identities before spending two weeks embedding them. When a leader stopped embedding social identities after embedding them for two weeks, group members' trust in their leader significantly reduced. When a leader started embedding social identities after not embedding them for two weeks, group members' perceptions of leader trust, leader influence and intentional mobilization significantly increased. Taken together, findings provide preliminary evidence that embedding social identities is beneficial for leader outcomes and intentional mobilization compared to a non-embedding leadership approach. Highlights: Embedding social identities involves translating group values into reality through language, activities and future practices. We explored the effects of embedding social identities experimentally across two studies in a sporting context. Embedding social identities relates to greater leader trust, influence and intentional mobilization, and lower conflict. Ceasing to embed social identities reduces leader trust. Altering leader behaviours to embed social identities increases leader trust, influence and intentional mobilization.